Ethical leadership and Gen Z: Enhancing work engagement through trust in Bandung city - Norina, Shafira; Sary, Fetty Poerwita (Edelweiss Applied Science and Technology, 2025)
Generation Z employees often face challenges in maintaining work engagement, which can negatively affect organizational performance. Ethical leadership has the potential to enhance employee engagement by fostering trust between leaders and employees. Ethical leaders, through their integrity and fairness, can build trust that indirectly promotes higher work engagement. This research aims to examine the effect of ethical leadership on work engagement among Generation Z employees in Bandung City, with a focus on the mediating role of leader trust. Specific objectives include assessing the levels of ethical leadership, work engagement, and leader trust, as well as determining the significance of their interrelationships. The research adopts a quantitative approach, utilizing Structural Equation Modeling (SEM) with LISREL for data analysis. A structured questionnaire was distributed to Generation Z employees in Bandung, and the collected data were analyzed to test the proposed hypotheses. The findings reveal that ethical leadership significantly and positively influences work engagement and leader trust. Additionally, leader trust has a significant positive effect on work engagement. Importantly, leader trust mediates the relationship between ethical leadership and work engagement, emphasizing the indirect impact of ethical leadership on employee engagement through trust. This research contributes to the understanding of the critical role of ethical leadership in fostering a trusting and engaging work environment for Generation Z employees. Organizations are encouraged to prioritize ethical leadership practices through targeted training programs, transparent decision-making, and policies that promote trust and engagement. Future research should explore additional variables, such as organizational culture and job satisfaction, and expand the research scope to different industries, regions, and employee demographics to validate and enrich these findings.